2017
DOI: 10.1186/s13048-017-0315-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of circulating ovarian cancer early detection markers and their contribution to discrimination of early detection models: results from the EPIC cohort

Abstract: BackgroundOvarian cancer early detection markers CA125, CA15.3, HE4, and CA72.4 vary between healthy women, limiting their utility for screening.MethodsWe evaluated cross-sectional relationships between lifestyle and reproductive factors and these markers among controls (n = 1910) from a nested case-control study in the European Prospective Investigation into Cancer and Nutrition (EPIC). Improvements in discrimination of prediction models adjusting for correlates of the markers were evaluated among postmenopau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…Age was nonlinearly associated with CA125 in our study, which is consistent with our prior study in EPIC in which we observed an inverse U-shaped association between age and CA125 levels among premenopausal women (9). Similarly, non-white race was associated with significantly lower CA125, which was consistent with prior studies in postmenopausal women (7,8), suggesting the need for different thresholds for minority populations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Age was nonlinearly associated with CA125 in our study, which is consistent with our prior study in EPIC in which we observed an inverse U-shaped association between age and CA125 levels among premenopausal women (9). Similarly, non-white race was associated with significantly lower CA125, which was consistent with prior studies in postmenopausal women (7,8), suggesting the need for different thresholds for minority populations.…”
Section: Discussionsupporting
confidence: 91%
“…We selected factors that have been previously reported to be associated with CA125 in at least one prior study (7)(8)(9)11), ovarian cancer risk factors (18), and several factors which were biologically plausible to be associated with CA125 (10). Those included age at blood draw, race, body mass index (BMI, kg/m 2 ), smoking status (never, former, current), pack-years calculated by number of packs of cigarettes per day multiplied by the number of years a person had smoked, age at menarche, oral contraceptive use and its duration (months), parity, self-reported endometriosis, tubal ligation, family history of ovarian cancer, prior personal cancer diagnosis, caffeine intake (mg), genital powder use, infertility, number of miscarriages, ectopic pregnancy, ever use of intrauterine device (IUD), fibroids, menstrual cycle regularity and days between last menstrual period (LMP), and blood draw (7)(8)(9)(10)(11). Furthermore, we evaluated additional variables related to menstrual characteristics and pregnancy timing: cycle length, days with menstrual bleeding, dysmenorrhea, age at first live birth, age at last live birth, and years since last live birth.…”
Section: Candidate Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this cohort, a nested case-control study of ovarian cancer was designed by matching each ovarian case ( n = 810) with up to four controls using incidence density sampling [13]. Among 1939 available controls, we defined postmenopausal women as those who met one of the following criteria at the time of blood draw: not on hormones and had not menstruated in the year prior to blood draw; on hormones and age 50 or greater; age at last menstruation was missing and age 50 or greater; had hysterectomy and age 50 or greater at the time of blood draw [7]. We excluded premenopausal women ( n = 485), women whose menopausal status could not be determined using the algorithm above ( n = 26), women without available CA125 measurement ( n = 12), and those missing information on candidate predictor variables of CA125 (total n = 555), leading to a total study population of 861 EPIC participants for this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, this is the first study that reported demographic characteristics in relation to CA125 values in healthy adolescents and young women. CA125 is known to be influenced by personal characteristics in healthy individuals [ 12 , 35 38 ], and only two studies have examined correlates of CA125 in premenopausal women, with the youngest age category being women age <30 years [ 12 , 35 ]. Consistent with prior studies, we observed that current smoking and hormone use at blood draw was associated with lower CA125, and blood draw at follicular phase was associated with higher CA125 in controls.…”
Section: Discussionmentioning
confidence: 99%